White-light interferometer with dispersion - an accurate fiber-optic sensor for the measurement of distance - Häusler, Gerd; et al. (Applied Optics, 2005)
We present a fiber-optical sensor for distance measurement of smooth and rough surfaces that is based on white-light interferometry; the sensor measures the distance from the sample surface to the sensor head. Because white light is used, the measurement is absolute. The measurement uncertainty depends not on the aperture of the optical system but only on the properties of the rough surface and is commonly ∼ 1 μm. The measurement range is approximately 1 mm. The sensor includes no mechanical moving parts; mechanical movement is replaced by the spectral decomposition of light at the interferometer output. The absence of mechanical moving parts enables a high measuring rate to be reached. © 2005 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.whitel